Pengaruh Celebrity Endorser dan Iklan Media Sosial Instagram Terhadap Keputusan Pembelian: (Studi Pada Pengguna Scarlet Whitening di Kota Samarinda) - Karmila; Sanjaya, Arwin (Universitas Sam Ratulangi, 2023)
The purpose of this research is to find out and analyze the effect of celebrity endorsers and Instagram social media ads on purchasing decisions for scarlet whitening products. The method used for this study was a quantitative method with 100 respondents in the city of Samarinda who used scarlet whitening products. The data was collected via a questionnaire. The data was then analyzed using validity and reliability testing techniques, classical assumption test, multiple linear regression, t-test, and f-test. The results of the study show that celebrity endorsers and Instagram social media advertisements have a significant effect on purchasing decisions on scarlet whitening products. Simultaneously, the variable celebrity endorser and Instagram social media advertising also significantly influence the purchasing decision of Scarlett Whitening products.